Recombination and restart at blocked replication forks. (December 2021) - Scully, Ralph; Elango, Rajula; Panday, Arvind; Willis, Nicholas A
Abstract : Replication fork stalling occurs when the replisome encounters a barrier to normal fork progression. Replisome stalling events are common during scheduled DNA synthesis, but vary in their severity. At one extreme, a lesion may induce only temporary pausing of a DNA polymerase; at the other, it may present a near-absolute barrier to the replicative helicase and effectively block fork progression. Many alternative pathways have evolved to respond to these different types of replication stress. Among these, the homologous recombination (HR) pathway plays an important role, protecting the stalled fork and processing it for repair. Here, we review recent advances in our understanding of how blocked replication forks in vertebrate cells can be processed for recombination and for replication restart.